Validation of real-time ultrasound technology for predicting fat thicknesses and ribeye areas of Brangus bulls from four months to two years of age - Waldner, D.N.; Schalles, R.R.; Olson, W.; Houghton, P.; Corah, L.R.; Dikeman, Michael E.; Unruh, John A. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Sixty Brangus bulls were evaluated live with two real-time ultrasound instruments to estimate ribeye area (REA) and 12th rib fat thickness (FT) every 4 mo beginning at 4 mo and 12 mo of age, respectively, and continuing until 24 mo of age. At each evaluation period 10 bulls were slaughtered to determine actual REA and FT. Scanned mean FT was accurate (P<.05) at 16 mo and was not different (P=.09) from the actual mean FT. Scanned mean REA was accurate (P<.05) at 12 mo. Absolute differences between scanned and actual mean FT and REA were different (P<.05) from zero for all main effects. Increased level of operator (scanner) skill did not improve accuracy of FT or REA measurements, whereas increased level of interpreter (reader) skill improved accuracy of REA measurements. There was no difference (P>.05) between the two ultrasound units in accuracy of estimating FT or REA. Scanned measurements overestimated bulls with less than .20 in FT and greater than 13.6 in2 REA and underestimated bulls with more than .40 in. FT and less than 12.0 in2 REA. We conclude that REA scanned at 12 mo and FT at 12 or 16 mo were sufficiently accurate to characterize groups of young bulls; however, individual scans were inaccurate. Scanning at other months was not accurate for either individuals or groups of young bulls.
Keywords: Beef; Bulls; Ultrasound; Ribeye Area; Fat thickness